Effect of pasak bumi (Eurycoma longifolia Jack), DHA, and seluang fish (Rasbora spp.) on neuroinflammation and neurotransmitter alterations in malnourished rats - Triawanti; Didik Dwi Sanyoto; Meitria Syahadatina Noor; Dimas Ikhsan Airlangga (Acta Biochimica Indonesiana, 2023)
Background: Malnutrition has detrimental effects on brain development, leading to neuroinflammatory and neurotransmitter disorders. A nutrient-rich diet is advocated to mitigate these effects. In South Kalimantan, natural resources such as pasak bumi (Eurycoma longifolia Jack.) and seluang fish (Rasbora spp.) are recognized for their potential antioxidant and anti-inflammatory properties. Objective: This study aimed to evaluate the effects of pasak bumi in comparison with seluang fish and DHA on neuroinflammation and neurotransmitter imbalances in malnourished rats. Methods: The study involved dividing malnourished rats into six experimental groups: (1) untreated control, (2) treated with pasak bumi extract, (3) treated with DHA, (4) treated with a combination of DHA and pasak bumi extract, (5) treated with seluang fish, (6) treated with a combination of seluang fish and pasak bumi extract; and a control group of normal rats receiving standard feed and placebo. The primary outcomes measured were levels of IL-6, TNF-α, and serotonin. Results: The study revealed that malnutrition in rats significantly elevated IL-6 and TNF-α levels. Treatments involving pasak bumi extract, both alone and in combination with DHA or seluang fish, reduced IL-6 levels. Similarly, combination of pasak bumi extract and DHA or seluang fish lowered TNF-α levels than single treatment of pasak bumi extract (p > 0.05). All treatments did not reduce the serotonin level. Conclusion: The findings of this study underscore the potent anti-inflammatory capabilities of pasak bumi extract, particularly when combined with DHA or seluang fish, in mitigating the inflammatory response in malnourished rats.